Comprehensive Evaluation Index System of Distribution Network for Distributed Photovoltaic Access - Xiao, Jinxing; Ye, Ying; Wang, Fa; Shen, Jieshi; Gao, Feng (Frontiers in Energy Research, 2022)
Affected by the light intensity and multiple adjacent stations, the output power of photovoltaic power stations presents the characteristics of randomness and correlation, which puts forward new requirements for the safe operation and planning evaluation of distribution network. Firstly, in order to accurately describe the randomness and fluctuation of photovoltaic output, a Gaussian mixture model based on improved optimal particle swarm optimization algorithm is proposed, and the joint probability density function of multiple photovoltaic output is solved; Then the power flow equation is linearized, the linear expressions of bus voltage and line power flow are derived, and the joint probability distributions of multi-node voltage and multi-line power flow are obtained respectively. Based on this, the reliability index and voltage quality index in the presence of the distributed renewable energy were constructed. Finally, the novel power grid planning evaluation index is tested in a real system of China, the combination weight is determined by analytic hierarchy process, and the comprehensive evaluation results are obtained. The simulation results prove the feasibility of the evaluation index system.